Characteristic of Silica Level (SiO3) Resulted from the Extraction of Rice Husk Ash with KOH Solvent towards the Amount of Heating Time - Wirawan, Riza; Hadi Sutrisno, Himawan; Ambarwati, Desi; Febriani, Andralisa (International Journal of Engineering and Technology, 2018)
Silica is widely available in nature including the ones in the form of crystal granule, gel and colloid. Silica is known to have a higher boiling point than other materials. The production of silica gel from rice husk ash has a characteristic in the amount of silicone level which depends on its heating time during extraction. This research aims at increasing production of silicone element in rice husk ash extraction method using kalium hydroxide (KOH), with heating time variation during its solution, namely between 15, 30, 45 and 60 minutes. With an observation using EDS, the relationship of heating time toward the silicone level on the resulted material can be discovered. The 15-minute heating time contains the highest silicone level compared to the 30, 45 or even 60-minute heating time.Â